Population dynamics, life stage and ecological modeling in Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) - Rosa, G. S. [UNESP]; Costa, M. I. S.; Corrente, J. E. [UNESP]; Silveira, L. V. A. [UNESP]; Godoy, W. A. C. (Entomological Soc Brasil, 2011)
In this study we investigated the population dynamics of Chrysomya albiceps (Wiedemann) with laboratory experiments, employing survival analysis and stage structure mathematical models, emphasizing survival among life stages. The study also assessed the theoretical influence of density dependence and cannibalism during immature stages, on the population dynamics of the species. The survival curves were similar, indicating that populations of C. albiceps exhibit the same pattern of survival among life stages. A strong nonlinear trend was observed, suggesting density dependence, acting during the first life stages of C. albiceps. The time-series simulations produced chaotic oscillations for all life stages, and the cannibalism did not produce qualitative changes in the dynamic behavior. The bifurcation analysis shows that for low values for survival, the population reaches a stable equilibrium, but the cannibalism results in chaotic oscillations practically over all the parametric space. The implications of the patterns of dynamic behavior observed are discussed.
Keywords: Population ecology; stage matrix; blowfly